Manajemen Pendidikan Pada Pementasan Wayang Kulit - Karoso, Subianto (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Leather puppet wltich is playe. by dalang is seen as an entertainment also contain life perceptia, behavior,ethic, norm, character, and life principles. Dalang as an artist alsofunction as educator for lhe community. In managingand leading leather puppet, he has to be able to apply managementfitnction well in order to performnicely, fluently, andsequencewith the planned, to satisly the audience.